Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2025)
Table of Content: 1. Agricultural production in the southern central Rif: between traditional practices and the desire for modernization and intensification "Taounate District as a model" Dr. Hini Mohammed, Dr. El-Bazoui Jaouad, Dr. Errafik Mohammed 2. Assessment of the Population Structure and Regeneration Status of Different Communities of Vachellia gerrardii in Al-Haski Valley, Al-Taysia Reserve, Kingdom of Saudi Arabia Mr. Maher Mohammad Bali,Prof. Ahmed Abdullah Al-Dughairi ,Dr. Ali Ebrahem Al-Zubaidi 3. The impact of urban expansion on the vegetation cover in the city of Baqaa using geographic information systems during the period (1990-2024 AD) Dr. Seham Sayer Khalif Al-Shammari